QIYAM AL-LAIL DALAM PERSPEKTIF RASULULLAH (Tuntunan Shalat Malam Ala Rasulullah SAW Serta Urgensinya Dalam Kehidupan Umat Manusia) - Mujiburrohman, Mujiburrohman (Universitas Islam Madura, 2014)
Qiyam al-Lail is the plural form of the word (idafah) in Arabic consisting of words and Qiyam al-Lail, whose meaning is the popularity of evening prayer. Qiyam al-Lail itself is a prayer which is done at night until dawn with nature, kaifiyat and certain cycles in accordance with the guidance of Allah and His Messenger. Qiyam al-Lail Included is the Witr prayer, praying tahajjud and tarawih prayers. Advocated Prophet Qiyam al-Lail implement, because the night prayer there are many benefits, among them draw closer to God Almighty, eraser ugliness and prevention of acts of sin. In addition, the evening prayer is also a major prayer after the obligatory prayer, where the presence of God in the middle of the night closer to his servant. This paper attempts to describe a comprehensive understanding of Qiyam al-Lail